Regional features of the brick art nouveau direction in the architecture of the city of Kharkiv (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2025)
The article considers the issue of stylistic attribution of buildings with decorative brickwork of facades within the Art Nouveau style in the city of Kharkiv. Modern trends in the reconstruction and preservation of facades of city`s historical buildings, in general, are considered. Negative trends in the state of preservation of the original image, integrity and completeness of facade solutions, even of buildings-architectural monuments of the city of local importance, are identified.Literature and other resources on the topic of the history of architecture of Kharkiv, the history of the Art Nouveau style and the brick style are analyzed. In particular, the dissertation of Ganna Korovkina “Features of the Art Nouveau architecture in Kharkiv city” (2020) is analyzed.Clarifications are proposed regarding the intra-stylistic attribution of buildings with decorative brickwork of facades within the Art Nouveau style of the city of Kharkiv, namely, the allocation of the corresponding buildings into an independent direction “brick Art Nouveau”.The history of the gradual degradation of Art Nouveau facades in Kharkiv during the last century, in general, and the buildings of the considered group, in particular, is highlighted. The specific problems of preserving the image and authenticity of the facades of buildings of suggested direction are described.The role of brick as the basis of facade decoration in world architecture history from antiquity to the 20th century is analyzed. The history of brickwork facades in architecture, urban planning, and the history of the city of Kharkiv from the time of its foundation to the present day is analyzed. The exceptional role of brick architecture of the Art Nouveau era in the formation of the architectural, construction, urban planning, and historical heritage of the city is emphasized.The principles of identification of buildings of the brick Art Nouveau direction are highlighted. A preliminary list of buildings of the direction is provided, which consists of 96 addresses, including 22 architectural monuments. The given group of buildings, according to preliminary calculations, constitutes about a quarter of all buildings of the Art Nouveau style in Kharkiv.Examples of architecturally correct reconstructions of buildings with the reveal of historical brick masonry are demonstrated. An example of controversial work with the facade of an Art Nouveau building with decorative brickwork (i.e. painting, additions, replacement of window frames) at 8 Bursatskyi Uzviz street is given, and a comparative preliminary design proposal for the reconstruction of the facade is provided, taking into account the decorative essence of the brickwork and Art Nouveau style principles.
Keywords: Art Nouveau; brick Art Nouveau; brick style; brickwork; Kharkiv; decorative masonry; facade; architectural monument; reconstruction; cataloging